The Professionalism of Ministry School Graduates Legally in Market Share - Ade Riusma Ariyana; Firdo Lingga (International Journal of Law Society Services, 2022)
Humans are a very important resource for the running of the wheels of government organizations. Without the human element that is essentially the planning, implementation and supervision of government organizations, of course, the goals that have been set will not be achieved. In order to have standards of ability, quality, quality and reliability in carrying out work tasks in accordance with the education, expertise and rank or class level possessed by each employee. Government agencies that have good and correct organizations supported by employees who carry out work in accordance with their main duties and functions will most likely not experience obstacles in carrying out their duties effectively (preferably or as much as possible). Human Resource Empowerment is an activity carried out to improve the ability of employees. Empowerment of Human Resources can be done through education and training both on the job site and off the job site, transfer or by way of promotion. This can be done with or without looking at the organizational structure. Willingness, motivation, and ability possessed by employees can be developed for the benefit of a government agency which is certainly related to the performance of apparatus employees in carrying out the duties, principals, and functions assigned to them.